1990
DOI: 10.1093/ajcn/52.6.987
|View full text |Cite
|
Sign up to set email alerts
|

Energy supplementation in the last trimester of pregnancy in East Java, Indonesia: effect on maternal anthropometry

Abstract: The effect of prenatal energy supplementation on maternal anthropometry was assessed in a controlled, randomized trial in Madura, East Java. At 26-28 wk of gestation women were either given 465 kcal/d (HE group) or 52 kcal/d (LE group). Two hundred seventy-six women were enrolled in the HE group and 266 women, in the LE group. Supplement intake was variable. Testing of effect by treatment and compliance was thus done by subcategories (HE 1-3 and LE 1-3, corresponding to less than 45, 45-89, and greater than or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…36 and 1550 kcal/day in Indonesian women. 37 The suboptimal nutritional status of mothers might have resulted in a preferential effect for the maternal compartment, the benefits for infants afterward involving other mechanisms such as better breast milk output and hence less morbidity as proposed by the authors in the Indonesian trial. 35 In the 2 studies, the effects on growth were indeed only observed in the postnatal period and not at birth.…”
mentioning
confidence: 99%
“…36 and 1550 kcal/day in Indonesian women. 37 The suboptimal nutritional status of mothers might have resulted in a preferential effect for the maternal compartment, the benefits for infants afterward involving other mechanisms such as better breast milk output and hence less morbidity as proposed by the authors in the Indonesian trial. 35 In the 2 studies, the effects on growth were indeed only observed in the postnatal period and not at birth.…”
mentioning
confidence: 99%
“…Supplementation trials and observational studies have shown a positive correlation between total energy intake and gestational weight gain in many countries, including Thailand, the United States, the Philippines, and Germany [6,8,12,24]. However, some studies, such as a trial in Indonesia [25], showed no relationship between total energy intake and weight gain during pregnancy. Similar to the results of our study, a review of 13 trials from many countries reported lower gestational weight gain with isocaloric protein supplementation [3].…”
Section: Discussionmentioning
confidence: 99%
“…The fat increase in pregnancy in these populations also tends to be smaller. For example, samples of pregnant women had no increase in fat in Bangladesh (Alam et al, 2003), an increase of 0.6 kg in the Philippines (Guillermo- Tuazon et al, 1992), 1.4 kg in Thailand (Thongprasert et al, 1987), and 1.5 kg in Java (Kardjati et al, 1990). One sample in the Gambia with especially limited nutrition had a loss of 4.7 kg of fat during pregnancy (Lawrence et al, 1987).…”
mentioning
confidence: 99%